Development and Evaluation of SmartFraction: An Integrated Problem-Based Fraction Learning Media for Enhancing Elementary Students' Numeracy Skills - Dahlia Ayu; Joko Sulianto; Muhtarom Muhtarom (Jurnal Pendidikan Terapan, 2026)
Purpose: Despite the widespread use of Problem-Based Learning (PBL), fraction manipulatives, and multiple mathematical representations, few learning media integrate these components to improve students' numeracy skills. Therefore, this study aimed to develop and evaluate SmartFraction, an integrated PBL-based fraction learning media by examining its validity, practicality, and effectiveness. Methods: This study employed a Research and Development approach using the ADDIE model, followed by a quasi-experimental pretest-posttest control group design. Participants comprised 23 fourth-grade students (12 experimental and 11 control). Data were collected through expert validation, response questionnaires, classroom observations, and numeracy tests. Data were analyzed using descriptive statistics, the Shapiro–Wilk test, Levene's test, an independent-samples t-test, normalized gain (N-Gain), and Hedges' g. Findings: SmartFraction demonstrated high validity (88.33%) and high practicality based on user responses. Students in the experimental group achieved significantly higher numeracy performance than those in the control group (p < 0.001). The experimental group achieved a moderate N-Gain (0.6487), whereas the control group achieved a low N-Gain (0.2387). Hedges' g (4.94) indicated a very large effect, although this result should be interpreted cautiously because of the relatively small sample. Overall, SmartFraction proved to be a valid, practical, and effective learning medium for improving students' numeracy skills. Research Implications: SmartFraction offers an effective alternative by integrating contextual problem solving, multiple fraction representations, and collaborative learning to strengthen numeracy. Originality: SmartFraction uniquely integrates PBL, multiple fraction representations, and numeracy-oriented tasks into a single learning medium, addressing a gap in previous fraction learning research.